Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island - Kocian, Matúš; Hlaváč, Peter (Zootaxa, 2018)
A review of all species of the genus Pseudolathra Casey, 1905 known from Réunion is presented. Five species are recorded and one species, Pseudolathra janaki Kocian & Hlaváč, sp. n., is described. New records for Pseudolathra gomyi (Lecoq, 1986) are given. Four species are illustrated and a key to all species is given.